Bronchopulmonary Dysplasia: Crosstalk Between PPARγ, WNT/β-Catenin and TGF-β Pathways; The Potential Therapeutic Role of PPARγ Agonists - Yves Lecarpentier; Elizabeth Gourrier; Vincent Gobert; Alexandre Vallée (Frontiers Media S.A., 2019)
Bronchopulmonary dysplasia (BPD) is a serious pulmonary disease which occurs in preterm infants. Mortality remains high due to a lack of effective treatment, despite significant progress in neonatal resuscitation. In BPD, a persistently high level of canonical WNT/β-catenin pathway activity at the canalicular stage disturbs the pulmonary maturation at the saccular and alveolar stages. The excessive thickness of the alveolar wall impairs the normal diffusion of oxygen and carbon dioxide, leading to hypoxia. Transforming growth factor (TGF-β) up-regulates canonical WNT signaling and inhibits the peroxysome proliferator activated receptor gamma (PPARγ). This profile is observed in BPD, especially in animal models. Following a premature birth, hypoxia activates the canonical WNT/TGF-β axis at the expense of PPARγ. This gives rise to the differentiation of fibroblasts into myofibroblasts, which can lead to pulmonary fibrosis that impairs the respiratory function after birth, during childhood and even adulthood. Potential therapeutic treatment could target the inhibition of the canonical WNT/TGF-β pathway and the stimulation of PPARγ activity, in particular by the administration of nebulized PPARγ agonists.